2017
DOI: 10.21475/ajcs.17.11.03.pne261
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of indigenous vegetable (Atriplex hortensis L.) from trans-Himalayan region of Ladakh (Jammu and Kashmir), India

Abstract: In the present study a total of one hundred thirty two accession of indigenous vegetable (Atriplex hortensis L.) collected from fifteen different Trans-Himalayan geographical regions of Jammu and Kashmir, India, were morphologically characterized for 6 qualitative and 15 quantitative traits following descriptors developed by the National Bureau of Plant Genetic Resource (NBPGR), New Delhi, India, during the year 2014 -2015. Multivariate analysis, principal component analysis (PCA), multidimensional scaling (MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The authors investigated twenty-seven diverse genotypes of vegetable Amaranth collected from different agro-climatic regions of India. Although the accessions investigated were from other species than the ones evaluated in the current study, the behaviour of these qualitative traits has been shown not to vary since they are from the same family [11]. The qualitative traits have been regarded as beneficial for characterising species germplasm [12].…”
Section: Discussionmentioning
confidence: 81%
“…The authors investigated twenty-seven diverse genotypes of vegetable Amaranth collected from different agro-climatic regions of India. Although the accessions investigated were from other species than the ones evaluated in the current study, the behaviour of these qualitative traits has been shown not to vary since they are from the same family [11]. The qualitative traits have been regarded as beneficial for characterising species germplasm [12].…”
Section: Discussionmentioning
confidence: 81%
“…The seeds and leaves of A. hortensis are edible and have been consumed since ancient times (good source of crude quality protein and vitamins) [ 27 ]. In addition, the extracts of A. hortensis are used in traditional medicine as a health tonic and diuretic; moreover, they are efficacious in the treatment of gout and tumors [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genus Atriplex (Amaranthaceae) comprises about 260 species of large herbaceous plants widespread throughout the world, especially in the arid and semi-arid regions of Europe, Asia, Africa, Australia, and North America [ 1 ]. The genus represents one of the oldest wild edible products; for example, species such as A. hortensis , A. partulacoides , and A. sagittata have been used for many centuries as a leafy vegetable [ 2 , 3 , 4 , 5 ]. Recent studies have shown that due to their high nutritional value and protein content, A. hortensis seeds can be a substitute for widely used quinoa seeds or cereal grains [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, A. halimus is listed among plant remedies for breast cancer [ 6 ], being also applied in diabetes [ 7 ], as a laxative and to relieve stomach pain [ 8 ]. A. crossifolia has been used to cure jaundice [ 9 ], while A. hortensis leaves are valued as a diuretic and purgative agent [ 3 ]. In turn, the entire A. sagittata plant has been recommended for diabetes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%